First report of the Eucalyptus gall wasp, Ophelimus maskelli (Hymenoptera: Eulophidae), an invasive pest on Eucalyptus, from the Western Hemisphere - Burks, Roger A.; Mottern, Jason L.; Waterworth, Rebeccah; Paine, Timothy D. (Zootaxa, 2015)
Ophelimus maskelli (Ashmead) (Hymenoptera: Eulophidae) was found in southern California, USA, on March 17, 2014, in Riverside County, University of California Riverside Campus (UCR), and has been common there since then. It has also been found in other locations in southern California, including San Diego County (San Diego Safari Park on November 1, 2014), and Orange County (Laguna Niguel Regional Park). Specimens collected from UCR were compared with voucher specimens of O. maskelli collected from Lazio, Italy, and were found to be conspecific. This represents the first report of O. maskelli from the Western Hemisphere.